WORKING PAPERS AS A TOOL FOR EFFECTIVE AUDITING OF SETTLEMENTS WITH SUPPLIERS AND CONTRACTORS - GAVRILENKO, Valentina; KROT, Iuliia; BRAZILII, Nataliia; PASTERNAK, Yaroslava (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Thе article examines the importance of auditing settlements with suppliers and contractors in the context of ensuring the reliability and validity of the enterprise's financial statements and improving the auditor's working documents, which will ensure high quality and efficiency of the audit. In particular, the author emphasizes that working documents are an integral part of auditing activities, which allow auditors to study financial documents in detail, establish dependencies and connections between various data, identify possible financial risks and shortcomings, and allow for effective cooperation with clients and management personnel, increasing the effectiveness of communication and cooperation between the parties. According to this, the author has developed a number of unified working documents that can be used during audits of suppliers and contractors of the enterprise. It is also recommended to take into account certain aspects when compiling and applying working documents that will help identify potential problems and shortcomings in the work of the enterprise. But it is necessary to remember that working papers cannot replace the professional assessment of the auditor and his expert knowledge, and also cannot solve all the problems associated with the audit, but they can help in increasing the efficiency and quality of the audit, since with such a combined approach to the audit, it is possible to achieve better results and obtain a more objective picture of the state of financial transactions.The results of this study are important for increasing the level of trust in audit services and ensuring reliable protection of the interests of stakeholders, will help auditors to more effectively conduct an audit of accounts payable at enterprises, reduce risks, properly organize work and ensure the quality of the audit.
Keywords: audit; evidence; documentation; control; creditors; inspection; contractors; suppliers; working papers